Autosomal recessive pathogenic MSTO1 variants in hereditary optic atrophy - Sylvie Gerber; Lola Lessard; Cécile Rouzier; Samira Ait‐el‐Mkadem Saadi; Roxana Ameli; Stéphane Thobois; Lucie Abouaf; Françoise Bouhour; Josseline Kaplan; Audrey Putoux; Antoine Pegat; Jean‐Michel Rozet (EMBO Molecular Medicine, 2023)
Graphical Abstract Gerber et al report 2 autosomal recessive pathogenic Misato homolog 1 (MSTO1) variants causing hereditary optic atrophy and raise concerns about a previously identified dominant variant of MSTO1 by Gal et al (2017).